Thyroid Hormone Changes in the Northern Area of Tianjin during the COVID-19 Pandemic - Dong Weiwei; Wu Bei; Wang Hong; Wu Cailan; Shao Hailin; Xu Donghong; Wang Xiaolai; Hao Zhaohu; Li Shijun; Tan Jian; Jia Qiang (International Journal of Endocrinology)
Purpose. This study aimed to determine whether and how stress-induced thyroid hormone changes occur during the COVID-19 pandemic in the northern area of Tianjin. Methods. This study comprised two groups of study subjects in Tianjin: before (2019) and during (2020) the COVID-19 outbreak. Subjects were included if they had FT3, FT4, and TSH concentrations and thyroid TPOAb or TgAb information available. People who were pregnant, were lactating, or had mental illness were excluded. We used propensity score matching to form a cohort in which patients had similar baseline characteristics, and their anxiety level was measured by the Hamilton Anxiety Rating Scale (HAMA). Results. Among the 1395 eligible people, 224 in Group A and 224 in Group B had similar propensity scores and were included in the analyses. The detection rate of abnormal thyroid function was decreased in pandemic Group B (69.2% vs. 93.3%, χ2 = 42.725, p<0.01), especially for hypothyroidism (14.29% vs. 35.71%, χ2 = 27.429, p<0.01) and isolated thyroid-related antibodies (25.89% vs. 38.39%, χ2 = 8.023, p<0.01). The level of FT4 (z = −2.821, p<0.01) and HAMA score (7.63 ± 2.07 vs. 5.40 ± 1.65, t = 16.873, p<0.01) went up in Group B; however, TSH (z = −5.238, p<0.01), FT3 (z = −3.089, p=0.002), TgAb (z = −11.814, p<0.01), and TPOAb (z = −9.299, p<0.01) were lower, and HAMA was positive with FT3 (r = 0.208, p<0.01) and FT4 (r = 0.247, p<0.01). Conclusion. People in the northern area of Tianjin during the COVID-19 outbreak were at an increased risk of higher FT4, lower FT3, and lower TSH. The HAMA scores increased in emergency situations and were positively correlated with the levels of FT3 and FT4.